A very mutinous people the struggle for North Carolina, 1660-1713 - McIlvenna, Noeleen, 1963- (University of North Carolina Press, 2009)
According to Noeleen McIlvenna, the true exemplars of egalitarian political values fled Virginia's plantation society late in the 17th century to create the first successful European colony in the Albemarle, in present-day North Carolina. Tapping into previously unused documents, McIlvenna explains how North Carolina's first planters struggled to impose a plantation society upon the settlers and how those early small farmers, defending a wide franchise and religious toleration, steadfastly resisted. She contends that the story of the Albemarle colony is a microcosm of the greater process by wh.